2013
DOI: 10.2341/11-442-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delaying Toothbrushing During Bleaching on Enamel Surface Roughness: An In Vitro Study

Abstract: SUMMARY This study aimed to evaluate the effect of toothbrushing on enamel surface roughness at three different intervals after daily bleaching treatment. Eighty enamel slabs were initially evaluated for surface roughness and then randomly divided into four groups. The bleaching procedure was carried out for 21 days, six hours daily. In the control group (group 1), the specimens were not brushed after bleaching, but in groups 2–4, they were brushed with toothpaste immediately, one hour, or two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
2
4
1
1
Order By: Relevance
“…These results were in accordance with previous studies (18)(19)(20) . They concluded that using bleaching gels with higher peroxide concentrations might cause surface alterations to the superficial enamel affecting its roughness.…”
Section: Discussionsupporting
confidence: 94%
“…These results were in accordance with previous studies (18)(19)(20) . They concluded that using bleaching gels with higher peroxide concentrations might cause surface alterations to the superficial enamel affecting its roughness.…”
Section: Discussionsupporting
confidence: 94%
“…Since abrasivity was the determining factor for surface roughness, postponing the brushing procedure 1 h after bleaching did not excert a protective effect for minimizing the surface roughness effects, contrarily as reported previously [39]. The irregularities caused by brushing probably were coarser than the supposed repairing action of saliva over the surface morphologic irregularities of bleached enamel and dentin.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, it can be hypothesized that prolonged exposure to a CBSD after dental whitening could further increase enamel roughness and decrease hardness. In a similar way, it has been observed that toothbrushing immediately after dental bleaching may increase enamel roughness 19 and that postponing oral hygiene for one or two hours after bleaching is advised 20 . It should be noted that if samples were stored in artificial saliva after bleaching, their ability of being stained could be reduced due to the potential remineralizing effect this solution.…”
Section: Discussionmentioning
confidence: 90%